A Framework for the Study of Positive Deviance in Organizations. Issue 11 (1st November 2016) - Mertens, Willem; Recker, Jan; Kohlborn, Thomas; Kummer, Tyge-F.
ABSTRACT: Positive deviance describes behavior that deviates from salient norms, yet is positive in its intention or effect. It has received considerable attention in the sociology literature, and is increasingly being studied in the context of the workplace. The development of a cumulative tradition in this domain, however, is hindered by the continued coexistence of multiple definitions of positive deviance in organizations and the use of various measurements and research designs. In this article, we synthesize existing definitions and approaches to the organizational study of positive deviance, integrate them into a coherent conceptual framework, and offer methodological advice and illustrations.